2020
DOI: 10.1186/s13052-020-00833-4
|View full text |Cite
|
Sign up to set email alerts
|

The psycho-social effects of COVID-19 on Italian adolescents’ attitudes and behaviors

Abstract: Background: COVID-19 is an emerging issue that has significant consequences on psycho-social well-being. Methods: In this regard, a survey was conducted on a large group of adolescents in Italy. The survey investigated four items: concerns and fears, information on the pandemic, provisions of public authorities (e.g., lockdown), and impact on everyday life. Results: Adolescents actively participated in the survey. COVID-19 affected emotions and lifestyle. COVID-19 influenced relationships with peers and parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
123
0
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(172 citation statements)
references
References 6 publications
17
123
0
15
Order By: Relevance
“…Research on COVID‐19 published early in the course of the pandemic echoes these findings: Limited studies in China suggest heightened levels of psychological problems and PTSD symptoms for some school‐aged children, adolescents, and young adults (Liang et al, 2020; Xie et al, 2019; Zhou et al, 2020), and studies of North American 13‐ to 18‐year‐olds link certain motivations for pandemic‐related social distancing (e.g., avoiding illness and judgment, being told to do so by friends) to greater anxiety and depressive symptoms (Oosterhoff, Palmer, Wilson, & Shook, 2020). In the academic domain, research on a nationally representative sample of Italian adolescents identified youth’s fears for negative educational consequences related to the COVID‐19 pandemic (Buzzi et al, 2020). Potentially linked to timing with high school graduation and decisions around postsecondary pursuits, educational worries, along with depressive symptoms and anxiety, may be higher during the COVID‐19 pandemic for those in higher grade levels in both China and Italy (Buzzi et al, 2020; Zhou et al, 2020).…”
Section: Life Course Perspective: Development Transitions and Trajementioning
confidence: 99%
See 1 more Smart Citation
“…Research on COVID‐19 published early in the course of the pandemic echoes these findings: Limited studies in China suggest heightened levels of psychological problems and PTSD symptoms for some school‐aged children, adolescents, and young adults (Liang et al, 2020; Xie et al, 2019; Zhou et al, 2020), and studies of North American 13‐ to 18‐year‐olds link certain motivations for pandemic‐related social distancing (e.g., avoiding illness and judgment, being told to do so by friends) to greater anxiety and depressive symptoms (Oosterhoff, Palmer, Wilson, & Shook, 2020). In the academic domain, research on a nationally representative sample of Italian adolescents identified youth’s fears for negative educational consequences related to the COVID‐19 pandemic (Buzzi et al, 2020). Potentially linked to timing with high school graduation and decisions around postsecondary pursuits, educational worries, along with depressive symptoms and anxiety, may be higher during the COVID‐19 pandemic for those in higher grade levels in both China and Italy (Buzzi et al, 2020; Zhou et al, 2020).…”
Section: Life Course Perspective: Development Transitions and Trajementioning
confidence: 99%
“…In the academic domain, research on a nationally representative sample of Italian adolescents identified youth’s fears for negative educational consequences related to the COVID‐19 pandemic (Buzzi et al, 2020). Potentially linked to timing with high school graduation and decisions around postsecondary pursuits, educational worries, along with depressive symptoms and anxiety, may be higher during the COVID‐19 pandemic for those in higher grade levels in both China and Italy (Buzzi et al, 2020; Zhou et al, 2020).…”
Section: Life Course Perspective: Development Transitions and Trajementioning
confidence: 99%
“…Another study reported that adolescents were influenced by COVID-19 concerning emotional aspects [87].…”
Section: Discussionmentioning
confidence: 99%
“…People's life, psychologically and socio-economically, is changing as an adaptation to this pandemic. Young adults are the age group that is almost ready to change their lifestyle and daily habits and are willing to adopt health protocols to keep life as safe and comfortable as possible in these pandemic conditions (Buzzi et al, 2020). Young adults better understand the development of technology which plays an important role in every aspect of life during this pandemic, apart from that young adults are indeed at a creative and spirited stage in their lives.…”
Section: Introductionmentioning
confidence: 99%